2008
DOI: 10.1253/circj.72.1125
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Early Recurrence and Delayed Cure After Catheter Ablation for Patients With Chronic Atrial Fibrillation

Abstract: Not achieving AF termination is the only independent predictor of ERAF. Among patients with ERAF, those with a smaller left atrium and AF termination have a higher probability of delayed cure. AF termination can independently predict delayed cure. These results emphasize the importance of AF termination during ablation for patients with chronic AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“… 974 Nevertheless, early recurrences have been shown to predict arrhythmia recurrences late after catheter ablation of AF in some patients. 260 , 329 , 935 , 976 , 977 , 978 …”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“… 974 Nevertheless, early recurrences have been shown to predict arrhythmia recurrences late after catheter ablation of AF in some patients. 260 , 329 , 935 , 976 , 977 , 978 …”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…27 These findings challenge the notion that recurrence during the 3-month blanking period is a transient and clinically insignificant result of periprocedural inflammation. 6,28 F I G U R E 1 Kaplan-Meier curves for LAVi and early recurrence. The cut-off of LAVi was obtained from survival tree analysis.…”
Section: Significance Of Early Recurrencementioning
confidence: 99%
“…Prior studies have identified clinical and demographic characteristics, arrhythmia characteristics, electrocardiographic and echocardiographic characteristics, and AF ablation procedural and post-procedural characteristics which are predict the development of ERAA after ablation, several of which we have listed in Table 1[2,5,7,10-22]. …”
Section: Predictors Of Eraamentioning
confidence: 99%